URANIUM IN GRANITIC MAGMAS: PART 2. EXPERIMENTAL DETERMINATION OF URANIUM SOLUBILITY AND FLUID-MELT PARTITION COEFFICIENTS IN THE URANIUM OXIDE-HAPLOGRANITE-H2O-NAX (X = CL, F) SYSTEM AT 770°C, 2 KBAR - Peiffert C.; Nguyen-Trung C.; Cuney M. (My University, 1996)
The solubility of uranium oxide was investigated in both aqueous halide (Cl, F) fluid and granitic melt in equilibrium in the system uranium oxide-haplogranite-H2O-NaCl (0.1 5.0 molal), NaF (0.1 0.5 molal) at 770°C, 2 kbar, and fO2 conditions controlled by Ni-NiO, Fe3O4-Fe2O3, and Cu2O- CuO buffers. Three distinct uranium oxides UO(2+x) with x = 0.01 ± 0.01; 0.12 ± 0.02; and 0.28 ± 0.02, respec- tively, were obtained in both chloride and fluoride systems, under the three fO2 conditions cited above. Changes in the composition of aqueous solutions and silicate melt were observed after the runs. These changes were more pronounced for the fluoride-bearing experiments. Quench pH decreased from 5.9 to 2.1 with increasing chloride molality from 0.085 4.38 molal. For fluoride solutions, the decrease of pH from 5.4 to 3.4 corresponded to the increase of fluoride molality from 0.02 0.23 molal. The U solubility in chloride solutions was in the range 10 967 ppm. For the same molality, fluoride solutions appeared to dissolve up to twenty times more uranium than chloride solutions. The increase of halide molality and oxidation led to increase the U solubility. The U solubility in silicate glasses was in the range 10-1.8 × 104 ppm and increased with increasing oxidation and halide concentration. In addition, increasing agpaicity also increased U solubility in the chloride system. This effect was not observed in the fluoride system. The chloride concentration in the silicate melt increased from 100-790 ppm with increasing initial aqueous chloride concentration from 0.1 5.0 m. The fluoride concentration in the silicate melt increased from 2.8 × 103 to 1.1 × 104 ppm with increasing initial fluoride concentra- tion from 0.1 0.5 m. In the chloride system, the partition coefficient of U (log D)(U)fluid/melt) increased from -1.2 0 with increasing agpaicity from 0.92 1.36, for increasing chloride concentration from 0.085-4.38 molal and for increasing fO2 from 10-15 to 10-4 bar. In the fluoride system, a linear correlation was established between the partition coefficient of U and the log fO2. In F-rich system, D(U)fluid/melt values was in the range 2.4 × 10-2-4.2 × 10-2 for increasing fluoride concentration from 0.02 0.22 molal and for the same increasing of fO2. In the chloride system, the partition coefficients of Na (D (Na)fluid/melt) and K (D) (K)fluid/melt) are in good agreement up to 1.0 m NaCl with the two linear equations established by Holland (1972) : D (Na)fluid/melt = 0.46 × (Cl)(m) (1) and D(Na)fluid/melt = 0.34 × (Cl)(m) (2). However, in initial 5.0 m NaCl, slopes of Eqns. 1 and 2 decreased to 0.41 and 0.16, respectively. Data obtained in the present study provide useful information for the understanding of the behaviour of U in the fractionation processes of halide rich magmas. Fluid/melt partition coefficients higher than one, favorable for the genesis of magmatic U mineralization, can be reached for peraluminous leucogran- ites in equilibrium with chloride-rich solutions.